The role of spatial analysis in livestock research for sustainable development - Notenbaert, An Maria Omer (Informa UK Limited, 2009)
The role of spatial analysis in livestock research for sustainable development is pervasive because its versatility supports livestock researchers at many stages of their work. Spatial analysis assists case study identification, characterizes the geographic context of research findings, and subsequently is used to assess the context for out-scaling purposes. Components of livestock systems and elements of their context and interrelationships can be characterized with an explicit spatial dimension. Output from spatial analysis linked to the results of simulation and optimization models provides support for decision-making. This is especially important where decisions involve different disciplines and interaction with a variety of experts usually working together in a sustainable development team.